Nylanderia of the World Part III: Nylanderia in the West Indies - Lapolla, John S.; Kallal, Robert J. (Zootaxa, 2019)
The diversity of the formicine ant genus Nylanderia is currently underestimated and largely undescribed. This includes the faunas of tropical regions where species richness is typically high. Here, the taxonomy of the West Indian Nylanderia fauna is revised for the first time. Fourteen new species are described, bringing the total number of species known from the region to 22. The new species are: N. bibadia, sp. nov., N. caerula, sp. nov., N. coveri, sp. nov., N. disatra, sp. nov., N. esperanza, sp. nov., N. fuscaspecula, sp. nov., N. lucayana, sp. nov., N. metacista, sp. nov., N. pini, sp. nov., N. semitincta, sp. nov., N. sierra, sp. nov., N. wardi, sp. nov., N. xestonota, sp. nov., and N. zaminyops, sp. nov. There are several introduced species in the region including the globally widespread Old World species N. bourbonica. Other introduced species are N. fulva, N. pubens, N. guatemalensis, and N. steinheili. The following new synonyms are proposed: fulva Mayr 1862 (= fulva cubana Santschi 1930); steinheili Forel 1893 (= steinheili minuta Forel 1893). An identification key is provided for the workers of Nylanderia found in the West Indies. Photomontage images are provided for the worker of each species and when available photomontage and SEM images are provided for males. This work represents another step forward in understanding the diversity of this widespread and commonly encountered ant genus.